2009
DOI: 10.1214/07-aihp160
|View full text |Cite
|
Sign up to set email alerts
|

Copolymer at selective interfaces and pinning potentials: Weak coupling limits

Abstract: We consider a simple random walk of length N , denoted by (Si) i∈{1,...,N} , and we define (wi) i≥1 a sequence of centered i.i.d. random variables. For K ∈ N we define ((γ −K i , . . . , γ K i )) i≥1 an i.i.d sequence of random vectors. We set β ∈ R, λ ≥ 0 and h ≥ 0, and transform the measure on the set of random walk trajectories with the HamiltonianThis transformed path measure describes an hydrophobic(philic) copolymer interacting with a layer of width 2K around an interface between oil and water.In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In fact, Theorem 1.3 has been generalized in [17] to a large class of disorder random variables (including all bounded random variables). A further generalization has been obtained in [21], in the case when, added to the copolymer interaction, there is also a pinning interaction at the interface, that is, an energy reward in touching the interface. We stress, however, that these generalizations are always for the copolymer model built over the simple random walk: going beyond the simple random walk case appears indeed to be a very delicate (albeit natural) step.…”
Section: Introductionmentioning
confidence: 94%
“…In fact, Theorem 1.3 has been generalized in [17] to a large class of disorder random variables (including all bounded random variables). A further generalization has been obtained in [21], in the case when, added to the copolymer interaction, there is also a pinning interaction at the interface, that is, an energy reward in touching the interface. We stress, however, that these generalizations are always for the copolymer model built over the simple random walk: going beyond the simple random walk case appears indeed to be a very delicate (albeit natural) step.…”
Section: Introductionmentioning
confidence: 94%
“…A related coarse-graining result is proved in Pétrélis [91] for a copolymer model with additional random pinning in a finite layer around the interface (of the type considered in Section 4). It is shown that the effect of the disorder in the layer vanishes in the weak interaction limit, i.e., only the disorder along the copolymer is felt in the weak interaction limit.…”
Section: Weak Interaction Limitmentioning
confidence: 84%

Lectures on random polymers

Caravenna,
Hollander,
Pétrélis
2011
Preprint
“…This result was first proved in [7] in the special case of the basic model of section 1, i.e., for the discrete copolymer model based on the simple random walk on Z, corresponding to α = 1 2 (in [17] one can find an argument to relax the assumption in [7] of binary charges and in [25] the case with adsorption is treated, cf. the end of section 1.5).…”
Section: Continuum Model and Weak Coupling Limitmentioning
confidence: 92%
“…Finally, it is natural to wonder what happens when a pinning interaction is added to the copolymer model, that is when not only the solvents are selective, but something special goes on at the interface (thus taking into account for example the lack of sharpness of the interface or the fact that impurities could be trapped at the interface). There are works on this model, often called copolymer with adsorption (see for example [25,27,34]), but the understanding is very limited: we refer to [15, § 6.3.2] for a detailed overview on this issue.…”
Section: The Critical Behavior and A Word About Pinning Modelsmentioning
confidence: 99%